STUDI PEMAHAMAN MASYARAKAT TENTANG MITAGASI BENCANA BANJIR BANDANG DI NAGARI UNGGAN KECAMATAN SUMPUR KUDUS KABUPATEN SIJUNJUNG - Dewita, Ratna; Dasrizal, Dasrizal; Erita, Yeni (Pendidikan Geografi, 2013)
The purpose of this research is to know the society Understanding Unggan Land SumpurÂ  Kudus subdistrict about the Flash Flash Flood Mitigation disasterThe kind of research to use the qualitative method, the research area doing in Unggan Land of Sumpur Kudus subdistrict of the Sijunjung regency.Reviewer of this research is Unggan society in Sumpur Kudus of the Sijunjung regency that have gotten the effect of flash flood disaster. The reviewer research use Snow Ball Sampling technique. The technicque of colleting data used are interview, observation, and documentation, analysis and data technique used are data reduction, data serving and conlusion collction.The result of this research that have done from the Unggan Land the society Understanding Unggan Land in Sumpur Kudus subdistrict about the flash flood mitigation is very less, Lees understanding of society about flash flood mitigation on Unggan Land in Sumpur Kudus subdistrict it caused that less of societyâs knowledge about disaster and mitigation, and also it caused that less of attention from the government about the socialitation of the flash flood mitigation on Unggan Land in Sumpur Kudus subdistrict. Where the governmentattention about the reconstruction that has broken and not only increasing of the sosiety understanding about how important of this flash flood disaster for society.